Internet der Dinge – Eine explorative Studie zur Diffusion von IoT im Kontext innovativer digitaler Wertschöpfungsmodelle und dem Kundennutzen aus Sicht von Experten - M. Fontanari; A. Nietiedt; M. Störkel (ISM Research Journal, 2019)
– Although IoT is already being used successfully and intensively in the business-to-business (B2B) sector and can be found under the term Industry 4.0 in particular, beneficial innovations in the business-to-consumer (B2C) sector have so far played only a subordinate role (cf. Bitkom 2015: 14–19; Platform Industrie 4.0 2014: 7–9). Overall, it should be noted that there is currently only a small number of value creation models for B2C compared to the much more diverse application areas and the resulting newer value creation in the B2B sector. Nevertheless, relevant studies and reports also predict a significant growth for IoT in the area of private consumers (cf. Initiative D21 2016: 24ff.; Kratzert et al. 2016: 3f.; Bitkom 2015: 3; Accenture 2014: 3). As a result, IoT will become increasingly relevant for end customers as part of sociological digitization. This study divides the IoT market for consumer devices based on the customer benefits and types of devices into four different segments: Time Savings, Security & Control, Health & Well-Being as well as Status & Entertainment. To assess these defined segments and to forecast the potential rollout speed, this study uses data of a two-staged Delphi-Survey with a total of 23 experts – mainly working in the telecommunications industry. The presented evidences in this paper are showing, especially devices within the segment for time saving use cases will rapidly diffuse through the consumer market. Followed by the segments of status and entertainment as well as the security & control, which both are not showing a significance for either a fast or slow rollout. Either way the findings clearly indicate, that devices for health and well-being, will potentially take a longer period of time to prevail in the market.
Keywords: 650